2004
DOI: 10.1292/jvms.66.1517
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis of Babesia gibsoni Infection in Dogs by an Improved Enzyme-Linked Immunosorbent Assay with Recombinant Truncated P50

Abstract: ABSTRACT. The surface antigen P50 of Babesia gibsoni is an important candidate for the development of a diagnostic reagent for canine piroplasmosis. In order to establish an effective diagnostic method for practical use, the gene encoding truncated P50 (P50t) lacking a signal peptide and C-terminal hydrophobic regions were cloned and expressed in Escherichia coli as a fusion protein with glutathione S-transferase (GST). More than 90% portion of the GST-P50t was expressed as a soluble form, in contrast with GST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Both the PCR and ELISA with GSTP50t tests used in this study have been reported to be sensitive and specific methods for the detection of B. gibsoni infection in dogs [8,20]. Using these tests, we detected B. gibsoni infection in 35 dogs from 8 prefectures in the eastern part of Japan.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Both the PCR and ELISA with GSTP50t tests used in this study have been reported to be sensitive and specific methods for the detection of B. gibsoni infection in dogs [8,20]. Using these tests, we detected B. gibsoni infection in 35 dogs from 8 prefectures in the eastern part of Japan.…”
Section: Discussionmentioning
confidence: 85%
“…ELISA: ELISA with GST-P50t was essentially carried out according to the protocol of Verdida et al [20]. Briefly, 96-well microplates were coated with the antigens, GST-P50t and GST (negative control), at a concentration of 250 ng per well.…”
Section: Samplingmentioning
confidence: 99%
“…Their homology with Bc28 suggests an erythrocyte binding ability, although no direct evidence has been reported. The use of the p50 recombinant protein in ELISAs revealed the presence of antibodies against this protein in dogs from the field (38). In addition, antibodies against recombinant p50 have been shown to inhibit the parasite development in a mouse model (39), and dog vaccination with both DNA coding for p50 and recombinant virus expressing p50 induces a weak protection against B. gibsoni parasites (40).…”
Section: Discussionmentioning
confidence: 99%
“…Serological tests like, indirect fluorescent antibody tests (IFAT), Indirectenzyme linked immunosorbent test are considered to be highly sensitive (Kaur et al, 2016), but only moderately specific because of antigenic cross-reactions to other Babesia spp (Yamane et al, 1993). The recent development of recombinant ELISA assays has improved test specificity (Verdida et al, 2004). Several PCR methods have been reported to diagnose B. gibsoni infection with high sensitivity and specificity (Birkenheuer et al, 2003;Inokuma et al, 2004).…”
Section: Introductionmentioning
confidence: 99%